COMPETENCE (SELF)ASSESSMENT INTERACTIVE SYSTEM OF TOMSK POLYTECHNIC UNIVERSITY ACADEMIC STAFF - Alfred A. Dul’Zon; Oksana M. Vasil’Eva (Высшее образование в России)
Competence (Self)Assessment Interactive System of Tomsk Polytechnic University’s (TPU) Academic Staff developed on the base of the competency model is presented. Reasons and aims of the system development are indicated. Stages and methods of the work, and interface requirements are briefly considered, and the problems of the system functioning at TPU are denoted. The feasibility of applying the competency model and the (self)assessment system constructed on its base for the solution of the problems of the University academic staff professional development, and increasing its effectiveness and quality of activities is substantiated.